Trace Elements Determination in Human Scalp Hair by Inductively Coupled Plasma Mass Spectrometry and Its Application to Health Status Assessment - Tan, Xijuan; Wang, Zhuming (European Journal of Applied Sciences, 2024)
In this paper, elements including Al, Cr, Mn, Fe, Cu, Zn, As, Se, Cd and Pb in scalp hair samples from five male adults in the age of 50 – 55 were accurately quantified by inductively coupled plasma mass spectrometry (ICP-MS). The ICP-MS quantification results were analyzed according to the recommendation from the Trace Element Research Council of China. It was found that the contents of Cr, As, Cd, and Pb were within the permitted ranges, while the concentrations of Mn, Fe, and Cu differentiated individually. It was worth noting that Fe contents in two samples were over 200 μg·g–1, which were higher than the highest permitted value of 130 μg·g–1. Interestingly, these two specimens also exhibited relatively higher concentrations of Mn and Cu. For Se, all five specimens showed slightly higher than the upper permitted value of 0.6 μg·g–1. But Al far exceeded the allowed 7.0 μg·g–1, yielding a ratio up to approximately 26-fold. It was also found that the content of Zn in one sample was out of the permitted range, giving about 13.5% lower than the least required concentration. It can thus be deduced that the participants having an accumulation of Mn, Fe, Cu, Se or Al were suggested to control the daily ingestion of these elements from foodstuff and/or medicine, while the participant showing Zn deficiency was recommended to take a reasonable amount of Zn supplements. From this study, all these participants were highly recommended to take a detailed check-up for the further health status assessment.